2015
DOI: 10.1080/15548627.2015.1072669
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of autophagosome-lysosome fusion in the buff mutant mice with the VPS33AD251E mutation

Abstract: -associated membrane protein 1; LRO, lysosome-related organelle; MAP1LC3/LC3, microtubule-associated protein 1 light chain 3; MEF, mouse embryonic fibroblast; RFP, red fluorescent protein; SNARE, soluble Nethylmaleimide-sensitive attachment protein (SNAP) receptor; SQSTM1/p62, sequestosome 1; STX, syntaxin; TH, tyrosine hydroxylase; VAMP, vesicle associated membrane protein/synaptobrevin; VPS, vacuole protein sorting; WT, wild type.The HOPS (homotypic fusion and protein sorting) complex functions in endocytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 42 publications
2
31
0
Order By: Relevance
“…Currently, patients with mutations in HOPS core components VPS11, VPS16 and VPS33A have been reported in literature, which all show a neurodegenerative phenotype (11,(67)(68)(69)(70)(71)(72)(73)(74). Moreover, during our studies, a third patient with compound heterozygote mutations in VPS41 was identified (Personal communication by I. Stolte-Dijkstra, University Medical Center Groningen), bearing the VPS41 R662* mutation as well as a missense mutation (VPS41 H466R ), and displaying a similar neurological phenotype.…”
Section: Discussionmentioning
confidence: 63%
“…Currently, patients with mutations in HOPS core components VPS11, VPS16 and VPS33A have been reported in literature, which all show a neurodegenerative phenotype (11,(67)(68)(69)(70)(71)(72)(73)(74). Moreover, during our studies, a third patient with compound heterozygote mutations in VPS41 was identified (Personal communication by I. Stolte-Dijkstra, University Medical Center Groningen), bearing the VPS41 R662* mutation as well as a missense mutation (VPS41 H466R ), and displaying a similar neurological phenotype.…”
Section: Discussionmentioning
confidence: 63%
“…Additionally, HOPS subunits were shown to interact with the autophagosomal SNARE, Stx17, which helps recruit HOPS to the autophagosome (Jiang et al, 2014; Takats et al, 2014). A role for the HOPS-Stx17 interaction in autophagy has subsequently been confirmed in a mouse model (Zhen and Li, 2015). HOPS has also been proposed to be linked to autophagosomes in mammalian cells by another Rab7 effector, Pleckstrin homology domain containing protein family member 1 (PLEKHM1).…”
Section: Tethers and Rabsmentioning
confidence: 87%
“…This has been shown for Vps3, Vps18, Vps33A and Vps41, and is likely the case for additional subunits. Point mutations and conditional knockouts, however, exhibit less-severe phenotypes, and allow researchers to study defects in animal models (Table S2) (Cai et al, 2016;Peng et al, 2012b;Suzuki et al, 2003;Zhen and Li, 2015). In addition, an increasingly growing range of phenotypes in patients is attributed to mutations in CORVET, CHEVI or HOPS components (Fig.…”
Section: Disease Phenotypesmentioning
confidence: 99%
“…Other causative genes for HPS encode AP-3 subunits, which we discussed above in the context of Vps41 function. The bf mouse mutation is particularly interesting because it leads to defects in LRO biogenesis and autophagy, while transport to lysosomes and lysosomal activity remains intact (Zhen and Li, 2015).…”
Section: Mutations In Vps33a Cause Hermansky-pudlak Syndrome and Mucomentioning
confidence: 99%